Bioinspired, Spine‐Like, Flexible, Rechargeable Lithium‐Ion Batteries with High Energy Density. Issue 12 (31st January 2018) - Qian, Guoyu; Zhu, Bin; Liao, Xiangbiao; Zhai, Haowei; Srinivasan, Arvind; Fritz, Nathan Joseph; Cheng, Qian; Ning, Mingqiang; Qie, Boyu; Li, Yi; Yuan, Songliu; Zhu, Jia; et al.
Abstract: The rapid development of flexible and wearable electronics proposes the persistent requirements of high‐performance flexible batteries. Much progress has been achieved recently, but how to obtain remarkable flexibility and high energy density simultaneously remains a great challenge. Here, a facile and scalable approach to fabricate spine‐like flexible lithium‐ion batteries is reported. A thick, rigid segment to store energy through winding the electrodes corresponds to the vertebra of animals, while a thin, unwound, and flexible part acts as marrow to interconnect all vertebra‐like stacks together, providing excellent flexibility for the whole battery. As the volume of the rigid electrode part is significantly larger than the flexible interconnection, the energy density of such a flexible battery can be over 85% of that in conventional packing. A nonoptimized flexible cell with an energy density of 242 Wh L −1 is demonstrated with packaging considered, which is 86.1% of a standard prismatic cell using the same components. The cell also successfully survives a harsh dynamic mechanical load test due to this rational bioinspired design. Mechanical simulation results uncover the underlying mechanism: the maximum strain in the reported design (≈0.08%) is markedly smaller than traditional stacked cells (≈1.1%). This new approach offers great promise for applications in flexible devices. Abstract : A spine‐like lithium‐ion battery, fabricated through a scalable and facile approach, demonstrates a stable cycle performance in different stress conditions, and high energy density compared to commercial batteries. It also presents a steady cycling under dynamic mechanical load testing. Simulation results uncover a much smaller strain tolerated for the design compared with that in a prismatic cell and a stacked pouch cell.